2011
DOI: 10.4103/2156-7514.82338
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Findings of Additional Malignant Lesions in Breast Carcinoma Seen by Second Look Ultrasound

Abstract: Objective:The aim is to show ultrasound (US) findings of additional malignant lesions of breast carcinoma visualized on targeted second-look US that were not identified by mammography or US prior to the time of diagnosis.Materials and Methods:A double-blind retrospective review of the US results from January 2008 through August 2010 of 228 patients with known breast cancer was conducted by two expert radiologists. The focus of the review was on the second-look US characteristics (following BI-RADS criteria) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 13 publications
(14 reference statements)
1
16
0
Order By: Relevance
“…Evaluation of the risk of bias and applicability of the included studies regarding the study purpose by using the QUADAS-2 tool demonstrated an unclear risk of bias owing to incomplete, nonconsecutive, or not-reported details on patient selection in six studies (14,15,23,24,26,27). Uncertainty regarding a reference-standard description, as well as the flow and timing of the study, were present in one study (26), whereas no risk of bias was found regarding the index test.…”
Section: Quality Assessment and Risk Of Biasmentioning
confidence: 74%
See 3 more Smart Citations
“…Evaluation of the risk of bias and applicability of the included studies regarding the study purpose by using the QUADAS-2 tool demonstrated an unclear risk of bias owing to incomplete, nonconsecutive, or not-reported details on patient selection in six studies (14,15,23,24,26,27). Uncertainty regarding a reference-standard description, as well as the flow and timing of the study, were present in one study (26), whereas no risk of bias was found regarding the index test.…”
Section: Quality Assessment and Risk Of Biasmentioning
confidence: 74%
“…Two studies (11.8%) included only patients with unclear MR imaging findings (27,28). The number of observers reading MR images and second-look US scans was not provided in four studies (15,17,23,26). Observer experience with US was given in only six studies (17,19,21,22,25,29), and observer experience with MR imaging was stated in another six studies (14,19,21,25,29,30).…”
Section: Study Design and Reportingmentioning
confidence: 95%
See 2 more Smart Citations
“…15,[19][20][21][22][23][24][25][26] Ultrasound lesion detection is influenced by lesion echo texture compared with breast background tissue and by lesion MRI appearance. A higher correlation of second-look ultrasound for mass lesions rather than non-mass ones has been reported.…”
Section: Discussionmentioning
confidence: 99%